Analyzing Conceptual Metaphors Through Michael Bublés ‘Call Me Irresponsible’ Album - I Kadek Roycke J. Kamandanu; Ida Ayu Made Puspani; Ni Ketut Alit Setianingsih (CV Wahana Publikasi, 2024)
The study “Conceptual Metaphor in Bublé’s Call Me Irresponsible Album” explores how metaphors in song lyrics can complicate understanding. This research categorizes and analyzes metaphor types found in Michael Bublé’s album, specifically focusing on 13 songs such as “The Best Is Yet to Come,” “Everything,” and “That’s Life.” Lyrics were sourced from Genius.com, and a descriptive qualitative approach guided by Lakoff and Johnson’s conceptual metaphor theory was employed. Three main types of conceptual metaphors structural, orientational, and ontological were identified in the analysis. Structural metaphors (56 instances), orientational metaphors (42 instances), and ontological metaphors (39 instances) were found to compare different concepts, often relating to themes of love and relationships. These metaphors contribute connotative, affective, and social meanings to the lyrics, influencing interpretations. The study highlights the importance of metaphor analysis in understanding how metaphors enrich song lyrics but also pose challenges in interpretation. By systematically categorizing and scrutinizing metaphors, this research enhances our comprehension of the nuanced meanings embedded in Bublé’s music, shedding light on the intricate interplay between language, metaphor, and thematic content in popular music.